2004
DOI: 10.1007/s00415-004-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in the first days of acute stroke

Abstract: Delirium was more frequent in stroke than in coronary acute patients. Among stroke patients, delirium was most frequent in older patients, in those with neglect, with medical complications and with intracerebral haemorrhages. These findings indicated that delirium in acute stroke patients 1) is not a non-specific consequence of acute disease and hospitalisation and 2) is secondary to hemisphere brain damage and to metabolic disturbances due to medical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
5
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 22 publications
9
128
5
3
Order By: Relevance
“…After controlling for confounding risk factors (higher age, dementia, disability on admission, increased CRP), delirious patients in our cohort had not a worse outcome, compared to similar patients without delirium. This is in contrast to other studies (Caeiro, Ferro, Albuquerque, & Figueira, 2004;Gustafson et al, 1991;Mitasova et al, 2012). Severely disabled, delirious patients have more complications and might have a worse rehabilitation on SU, even in short episodes of delirium.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…After controlling for confounding risk factors (higher age, dementia, disability on admission, increased CRP), delirious patients in our cohort had not a worse outcome, compared to similar patients without delirium. This is in contrast to other studies (Caeiro, Ferro, Albuquerque, & Figueira, 2004;Gustafson et al, 1991;Mitasova et al, 2012). Severely disabled, delirious patients have more complications and might have a worse rehabilitation on SU, even in short episodes of delirium.…”
Section: Discussioncontrasting
confidence: 91%
“…Most positive screenings were during the night, hence screening rates of other studies, which used a once per day assessment, might have underestimated delirium prevalence (Caeiro et al, 2004;McManus et al, 2009;Miu & Yeung, 2013;Oldenbeuving et al, 2011). The assessment instrument CAM was used in other studies with patients after stroke, too with results of 10% (Dahl et al, 2010), 12% (Oldenbeuving et al, 2011), 27% (Miu &Yeung, 2013), and28% (McManus et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The designs employed in the studies included in this review were prospective studies (n=11), retrospective studies (n=3) case controls (n=3), one cross sectional study, one pilot study of treatment intervention and one study which was described as "observational" (see table 2). A total of 12 studies reported applying established diagnostic criteria when assessing patients for delirium: Six (30%) studies applied DSM IV[2, [23][24][25][26][27], three (15%) studies applied DSM III-R [28][29][30], two studies applied DSM IV-R [31,32], and one (5%) study applied DSM III [33]. Three studies referred to "clinical assessment" but did not detail any diagnostic guidelines [34][35][36], and one study referred to the diagnosis of "disorientation" using a simple 3 point scale [37].…”
Section: Description Of Studies Included In This Reviewmentioning
confidence: 99%
“…Three studies referred to "clinical assessment" but did not detail any diagnostic guidelines [34][35][36], and one study referred to the diagnosis of "disorientation" using a simple 3 point scale [37]. As for tools used to screen for delirium, of the 14 studies utilising such tools, 5 used the DRS or DRS R-98[2, 23,24,31,32]; 2 studies used the CAM[,38]; 2 studies used both the DRS and the CAM [39,40]; 3 studies used the OBS Scale [25,29,30] and 2 studies used the MMSE [35,36]. See table 2 for full details.…”
Section: Description Of Studies Included In This Reviewmentioning
confidence: 99%
See 1 more Smart Citation